(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the emergence and development of consumer geography and the concepts of consumer basket are analyzed and appropriate conclusions are drawn. Also, the tasks of the science of consumer geography, the values of determining the rational norm of the consumer basket were studied.